Healing Touch Intervention in Obstetrics: Influence on Endorphin Levels and Active Labor Phase Duration - Sartika, Yan; Hevrialni, Rully; Daiyah, Isrowiyatun; Kundarti, Finta Isti (Poltekkes Kemenkes Palu, 2024)
Introduction: Anxiety during labor can disrupt maternal homeostasis and prolong the labor process, leading to complications for both mother and baby. Healing touch therapy is a complementary method aimed at reducing anxiety and facilitating labor progression, but its effects on physiological outcomes like endorphin levels and labor duration require further investigation. Objective: This study aimed to evaluate the effect of healing touch therapy on endorphin levels and the duration of the active phase of the first stage of labor. Methods: A pre-experimental one-group pre-post-test design was used. A total of 40 pregnant women were divided into control (n=20) and intervention (n=20) groups. The intervention group received healing touch therapy three times for 30 minutes. Blood samples were taken before and after the therapy to measure endorphin levels, and labor duration was recorded. Results: Mann-Whitney tests showed no significant change in endorphin levels after healing touch therapy (p=0.379). However, the duration of the active phase of labor was significantly shorter in the intervention group (median: 254.5 minutes) compared to the control group (280 minutes) (p=0.005). Conclusion: While healing touch therapy did not significantly impact endorphin levels, it effectively reduced the duration of the active phase of labor, suggesting its potential to support labor progression. Further research is needed to confirm these findings.